2022
DOI: 10.1186/s40164-022-00296-9
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells in hematologic malignancies: two sides of the same coin

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of bone marrow cells originating from immature myeloid cells. They exert potent immunosuppressive activity and are closely associated with the development of various diseases such as malignancies, infections, and inflammation. In malignant tumors, MDSCs, one of the most dominant cellular components comprising the tumor microenvironment, play a crucial role in tumor growth, drug resistance, recurrence, and immune escape. Although the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 160 publications
(170 reference statements)
1
7
0
12
Order By: Relevance
“…12 In addition, this study also found that the ILC2s-MDSCs axis was positively correlated with PD-L1 and PD-L2. Consistently, it has been reported that the increase of ILC2s and MDSCs further promotes the increase of PD-L1, 29 leading to resistance to the immune checkpoint inhibitors. Liu et al found that MDSCs enhanced their immunosuppressive function in breast cancer by activating the PI3K/AKT signaling pathway through PD-1/PD-L1.…”
Section: Discussionsupporting
confidence: 66%
“…12 In addition, this study also found that the ILC2s-MDSCs axis was positively correlated with PD-L1 and PD-L2. Consistently, it has been reported that the increase of ILC2s and MDSCs further promotes the increase of PD-L1, 29 leading to resistance to the immune checkpoint inhibitors. Liu et al found that MDSCs enhanced their immunosuppressive function in breast cancer by activating the PI3K/AKT signaling pathway through PD-1/PD-L1.…”
Section: Discussionsupporting
confidence: 66%
“…[13] MDSCs can inhibit T cell function in various ways, including the production of immunosuppressive molecules such as arginase 1, inducible nitric oxide synthase, reactive oxygen species, and peroxynitrite. [13,14] Moreover, MDSCs induce differentiation and/or proliferation of Foxp3 + regulatory T cells (Tregs). [15] Studies have demonstrated that MDSCs strongly inhibit the antitumor activities of T and NK cells and stimulate Tregs, leading to tumor progression.…”
Section: Mdscsmentioning
confidence: 99%
“…(2) Brimnes et al (38) relataram pela primeira vez um aumento no número de MDSC no sangue periférico de pacientes com MM em comparação com controles saudáveis em 2010. (38,39) Mais tarde, Wang et al (40) mostraram que os níveis de M-MDSC estavam positivamente correlacionados com a recidiva do MM e negativamente correlacionados com os desfechos do tratamento. (39,40)…”
Section: Mdsc E Câncerunclassified
“…(38,39) Mais tarde, Wang et al (40) mostraram que os níveis de M-MDSC estavam positivamente correlacionados com a recidiva do MM e negativamente correlacionados com os desfechos do tratamento. (39,40)…”
Section: Mdsc E Câncerunclassified
See 1 more Smart Citation